Product Quality and Service Quality on Purchase Decisions for Fashion Products Online Through Perceived Risk in Social Commerce - Haekal, Azwar; Pranowo, Agus Setyo; Limakrisna, Nandan (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
This study aims to examine the influence of product quality and service quality on online fashion purchase decisions, with perceived risk serving as a mediating variable in the context of social commerce. The rapid growth of online shopping through social media platforms, particularly Facebook and Instagram, has transformed consumer behavior and introduced new dimensions of trust, risk perception, and purchase decision-making. This research investigates how consumers evaluate the reliability of products and services when making purchase decisions in digital environments where physical interactions are absent. Using a quantitative explanatory method, data were collected through questionnaires distributed to students of the Master of Management Program at Pakuan University who actively use Facebook and Instagram for online fashion transactions. A total of 120 valid responses were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test both direct and indirect effects among variables. The findings indicate that both product quality and service quality have significant positive effects on consumers’ purchase decisions. Moreover, perceived risk partially mediates the relationship between these variables, suggesting that higher product and service quality can reduce consumer uncertainty and enhance confidence in online purchasing. This implies that building perceived reliability and minimizing transaction risk are critical strategies for increasing customer engagement and satisfaction in social commerce. The study contributes to the growing literature on digital consumer behavior by integrating quality dimensions and risk perception into a unified model of online purchase decision-making. Practically, it provides managerial insights for social media entrepreneurs and e-commerce marketers to strengthen consumer trust through superior product offerings and responsive online services.